Functional characterization of DcMYB11, an R2R3 MYB associated with the purple pigmentation of carrot petiole - D’Amelia, Vincenzo; Curaba, Julien; Abid, Muhammad Ali; Esposito, Salvatore; Cavagnaro, Pablo; Carputo, Domenico; Iorizzo, Massimo (Springer, 2023)
The accumulation of anthocyanin pigments can exhibit different patterns across plant tissues and crop varieties. This variability allowed the investigation of the molecular mechanisms behind the biosynthesis of these pigments in several plant species. Among crops, carrots have a well-defined anthocyanin pigmentation pattern depending on the genic background. In this work, we report on the discovery of DNA structural differences affecting the activity of an R2R3 MYB (encoded by DcMYB11) involved in anthocyanin regulation in carrot petiole. To this end, we first verified the function of DcMYB11 using heterologous systems and identified three different alleles which may explain differences in petiole pigmentation. Characterization of the DcMYB11 alleles at the 5' upstream sequence unveiled a sequence that functions as a putative enhancer. In conclusion, this study provides novel insight into the molecular mechanisms controlling anthocyanin accumulation in carrot. By these outcomes, we expanded our knowledge on the cis-regulatory sequences in plants.